(untitled) (diségno, 2026)
The design of the Guggenheim Museum had a long and troubled history. The building was strongly opposed by supporters of the International Style due to its revolutionary and innovative nature [1], but Frank Lloyd Wright strenuously defended his idea, presenting it to public opinion as the only example of Organic Architecture [2] in New York [Dal Co 2004, p. 27]. The initial planning constraints were roughly the following: having to build no further than Midtown, the building would have belonged to the rigorous New York Hippodamian grid, so, in spite of himself, Wright was forced to fall back on the idea of a compact and vertical museum. [read more]